Measurement of the Radiation Energy in the Radio Signal of Extensive Air Showers as a Universal Estimator of Cosmic-Ray Energy - Allekotte, Ingomar; Almela, Daniel Alejandro; Asorey, Hernán Gonzalo; Bertou, Xavier Pierre Louis; Dasso, Sergio Ricardo; Dova, Maria Teresa; Etchegoyen, Alberto; Figueira, Juan Manuel; Filevich, Alberto; Freire, Martín Miguel; Garcia, Beatriz Elena; Golup, Geraldina Tamara; et al. (American Physical Society, 2016)
Fil: Allekotte, Ingomar. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Instituto Balseiro; Argentina